The Existence Of Bank Syariah Indonesia Post-Merger In Denpasar City - Rahmad Kurniawan; Sofyan Hakim; Novi Angga Safitri (Jurnal Ilmiah Ekonomi Islam, 2023)
The Islamic Banking Revolution is a fairly basic change in a field of Islamic financial institutions that unites the 3 largest Islamic banks in Indonesia, namely Bank Mandiri Syariah, Bank BRI Syariah and Bank BNI Syariah which merge or merge into one called Bank Syariah Indonesia. This new breakthrough regarding the merger of state-owned banks is expected to be a breath of fresh air for all circles, especially non-Muslims to be more receptive to Islamic banking. It is certainly hoped that all Indonesian citizens regardless of their religion can accept Islamic banking as an economic system in Indonesia, especially in the city of Denpasar, which is an Islamic minority. The universal nature of Islamic banks for all people, it is necessary to expand to non-Muslim communities in order to maintain the sustainability and existence of Islamic banks.This research is a field research using qualitative research methods, while the subjects of this research are the internal parties of the Indonesian Islamic Bank in Denpasar City and the community/customers of BSI Denpasar City. Data collection techniques in this study used observation, interviews and documentation techniques. The data validation technique uses credibility test with source triangulation and dependability test.The results of this study indicate that 1) The existence of the Post-Meger Indonesian Islamic Bank in Denpasar City is still able to survive due to their strategy that covers several aspects by implementing the steps taken by Bank Syariah Indonesia in order to continue to exist and survive during the pandemic. Its existence is by implementing the Financing Relaxation program to Reduce Bad Credit Post Mergers during the pandemic, Actively sharing in Community Activities during the pandemic, Business Strategy of Bank Syariah Indonesia Post Mergers during the pandemic (both in terms of survival and marketing by targeting potential customers). 2). The public perception of Denpasar City about the existence of Bank Syariah Indonesia after the merger, both in terms of improving product quality and improving service quality, can be seen from the public perception about the merger of 3 Islamic banks (BSI) is quite good, the majority of Denpasar people already know about the merger of 3 Islamic banks. (BSI). They strongly support this merger because it makes it easier for them to deal with the bank concerned because there are more branches and the reach to the bank is getting closer, both for products and services.